Couple found approaching UUM students to exchange BB1M vouchers for cash - New Sarawak, Tribune (New Sarawak Tribune, 2012)
Police have identified a couple to approached Universiti Utara Malaysia (UUM) students in Sintok, Kedah to exchange their 1Malaysia Book Vouchers (BB1M) for cash.